Optimizing the Performance of the South Kalimantan Unit through Traffic Dikmas in Order to Reduce Traffic Violations in the Legal Area of ​​the Pekalongan Police - Arya Dhaffa Rahmadina Putra Arya Dhaffa (Tanggon Kosala, 2022)
The traffic unit is a functional technical unit for the Police which is tasked with maintaining and overseeing all activities that occur in traffic so as to create security and public order in traffic and handle the many traffic violations. Based on the accumulation calculations that have been carried out by the Pekalongan Resort Police in the jurisdiction of the Pekalongan Police, the number of traffic violations is still relatively high. the community to increase public understanding and awareness regarding traffic rules. Dikmas activities require active participation and contribution from the community so that the main objectives of Dikmas Then activities are compliance and obedience to traffic rules and suppressing the number of traffic violations so that security, safety, order and smooth traffic can be realized. However, in fact the performance of the Kamsel Unit through Dikmas Lantas in the Pekalongan Polres jurisdiction is still not optimal, so the authors are interested in examining why the Kamsel Unit's performance through Dikmas then in order to reduce traffic violations in the Pekalongan Polres jurisdiction is not yet optimal? This study uses a qualitative approach and the research focus is holistic. The author's research location is in the jurisdiction of the Pekalongan Police. The data collection technique used is data triangulation technique by means of interviews, observation, document study and data validity. so it will be analyzed using the constant comparative method Based on the results of the data analysis carried out, the Kamsel Unit in the activities of Dikmas Lantas in the jurisdiction of the Pekalongan Police has been carried out properly and in accordance with the standard operating procedures stipulated in the Pekalongan Resort Police Regulation Number 1 of 2022, but its implementation cannot be said to be optimal because there are still obstacles. so that if these matters are not immediately addressed it will affect the level of traffic violations.